A methods engineering study on Botas Manufacturing Corporation - Ben, Rolly D.; Manienido, Michelle V.; Masilungan, Juvylyn M. (Diliman, Quezon City College of Engineering, 2001)
This work study employs methods engineering tools and applications to determine, analyze, and solve existing sources of deviations in the production system of Botas Manufacturing, Corporation. As one of the players in the country's shoe-producing industry, Botas supplies hot-weather boots to the nation's military forces and safety shoes to various construction industries. Hot weather boots comprise 84 percent of the company's total production. It is on the grounds that this study focuses mainly on this concern. Through scheduled plant visits, brainstorming sessions, and a detailed systems review, the team came up with Bottleneck process at the lasting section as the root deviation. From the eight sections comprising the production department, it was immediately observable that the number of work-in processes at the lasting section severely exceeds those of the other sections. Five root causes of the main deviation were determined from the ISHIKAWA diagram : inefficiency of plant layout, ineffectiveness of storage system, machine breakdown, imbalanced assembly line, insufficiency of the number of workers. Each cause is thoroughly discussed and sufficiently justified by theoretical and analytical discussion. All five causes may not be generalized for all sections in the production department, but all were observed to exist in the lasting section. The team devised several layouts to replace the existing workstation assembly at Lasting. Each layout was thoroughly evaluated with respect to the distance cut off, material handling time and costs saved, and worker condition. A new layout, a combination of the serpentine and straight line layouts, is posed for recommendation. For the major problem of machinery breakdown, the team has determined the stapling machine as causing the greatest deviation. The machine's driver broke down at the greatest frequency over the period of study. A cost benefit analysis was conducted and three alternatives were devised : acquisition of a new staple machine; stock up on spare parts; maintain the current staple machine. From the analysis, the team recommended the acquisition of a new staple machine as the optimal choice to increase the section's efficiency at the lowest possible cost. The insufficiency of the number of workers (on the average, 12 per day), compensates for some of the bottleneck operations within lasting. It was observed that some workers attend to two operations at a time, causing work - in processes to build up at one station. With 15 operations currently in hand, the team posed the following alternatives for evaluation : increase worker number from 12 to 15, work overtime (60 minutes, 120 minutes), The recommendation of increasing the number of workers was determined to incur a greater production capacity increase than having operators work overtime. The team was unable to provide a Decision Analysis for Imbalanced Assembly Line because generating alternatives to the latter would lead to combining operations in one workstation, which is determined to be not beneficial in view of the systems review. Lastly, the team has suggested several temporary storage structures. Because the movement of work-in processes within the section occurs by LOTS, where one lot equals 13 pairs of HWB, the team searched for containers adhering to this system. An implementation period of six months is suggested in the last course of this study. Further, a special committee gathered for the purpose of improving the efficiency of the lasting section is recommended.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis